Educação empreendedora: análise dos temas abordados no ensino fundamental, médio e superior - Zambon, Sueli Aparecida (2014)
Although many efforts have been made to the spread and consolidation of an education that develops individuals more entrepreneurial, there is no consensus or objective guidelines in the literature regarding the topics that should be part of entrepreneurial education, or skills that must be developed. This research aims to seek a better understanding as to the themes and skills that comprise the Entrepreneurial Education. A set of representative experiments of entrepreneurship education was observed in the subjects and skills covered. Data were organized in a form, enabling the identification and comparison of trends by type of education - primary, secondary and higher education, and courses with no relationship with formal education. The results indicate that in elementary school the focus is on Entrepreneurial Behavior. In secondary school, there is a less marked trend in Entrepreneurial Behavior. In Brazilian higher education, there is a balance between the business group and the Entrepreneurial Behavior. In the experiences in higher education abroad, the trend is on Entrepreneurial Behavior. In courses with no ties to formal education has not been possible to identify a conclusive trend, although a greater number of issues have been cited in Business group. Considering all experiments, regardless of the stage or type of education in the Entrepreneurial Behavior group, the most frequently cited issues were Network Relationships, Creativity, and Autonomy. In the business group, the most cited topics were Marketing, Business Plans and Financial Planning. This research helped to provide a better understanding as to the themes and skills that comprise the Entrepreneurial Education, systematizing data, enabling comparisons and identifying trends and the most frequently cited issues in primary, secondary and higher education, and in courses with no relationship with formal education.